Eurasian empires as blueprints for Ethiopia - Asnake Kefale, 1970- author.
1 online resource.
Keywords: "This book is a contribution to the global history of the transfer of political ideas, as exemplified by modern Ethiopia. Ethiopia was never successfully colonized, leaving its ruling elite free to select a model of 'modern' (western) statehood. The politics of modern Ethiopia is marked by the tension between the two opposed models of the type of statehood explored in the book: the unitary, ethnolinguistically homogenous nation-state from Japan, in turn copied from the German Empire and the Soviet model of ethnolinguistic federalism. It is useful for scholars of Ethiopian and African history and politics, and offers a case in comparative studies on models of national statehood elsewhere"--